PENGARUH STRATEGI BELAJAR MIND MAPPING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATERI MENYUSUN DAN MENGANALISIS RANCANGAN MENU WANITA HAMIL DAN MENYUSUI DI SMK KATOLIK MATER AMABILIS SURABAYA - EKA PURWANINGSTYAS, KEZIA (Jurnal Tata Boga, 2017)
Abstract: The learning process of dietetics at SMK is such an important thing. One of the factors that affects it is the use of learning strategy which should be suitable for the learning materials. The learning strategy used in this study is mind mapping. This study aimed to find out the effect of mind mapping implementation toward: 1) activity in learning process; 2) students’ activity; 3) the students’ learning outcome; 4) the students’ respond in Planning and Analyzing a Diet for Pregnant and Breastfeeding Women at SMK Katolik Mater Amabilis Surabaya. This study used Quasi Experimental Design One Group Pretest-Postest. The subjects of this study consisted of 34 students of tenth grade of SMK Katolik Mater Amabilis Surabaya. The data collection used observation, test, and student questionnaire. Data analysis technique used the Paired Sample t-test data analysis The analysis result showed that 1) the implementation of mind mapping went effectively and systematically, seen from the average score of teacher’s activity which reached 3.56; 2) the implementation of map mapping toward the students’ activity reached the average score of 3.5 which can be categorized as ‘good’ with the conclusion of that the learning process corresponded the observed aspects;3) the effect of mind mapping implementation toward students’ learning outcome covering the students’ attitude and knowledge aspects is considered greater, compared to the lecture method, which is showed by the significant average result; 4) the effect of mind mapping implementation toward the students showed the average score of 97.02. According to the result, it can be concluded that there is effect of mind mapping implementation in Planning and Analyzing a Diet for Pregnant and Breastfeeding Women toward the students’ learning outcome at SMK Katolik Mater Amabilis Surabaya. Keywords: learning strategy, mind mapping, learning outcome